Pelatihan Penerapan Design Thinking untuk Meningkatkan Kompetensi Kreatif dan Pola Pikir Peserta Didik - Kesumawati, Nila; Destiniar, Destiniar; Misdalina, Misdalina; Fahriza Fuadiah, Nyiayu; Marhamah, Marhamah; Aulia, Ananda; Ayu Septiani, Widya (PELITA NUSA TENGGARA, 2025)
Design Thinking is a creative approach to solving human-centered problems, emphasizing empathy, ideation, prototyping, and testing solutions. This approach is useful in creating student-centered learning innovations, providing positive experiences, and increasing learning engagement and outcomes. In the context of education, Design Thinking helps educators understand student needs through five stages: empathy, definition, ideation, prototype, and testing. Implementation of this method allows learning to be more effective, efficient, and interesting. This Community Service (PkM) is designed to socialize the concept of Design Thinking to educators through the delivery of materials and direct practice. The stages of activity include preparation, implementation: pretest, delivery of materials along with examples of design thinking concepts, creating interview instruments, reflection, and posttest, and program evaluation. Participants are trained to understand the concept of Design Thinking, identify implementation challenges, and create instruments to find and solve educational problems. The results obtained from this PkM activity are: (1) the average increase in understanding of the material on Design Thinking using N-Gain is 0.50, included in the moderate category (2) recapitulation of participant satisfaction with the PkM activities that have been carried out by the PkM team of the Mathematics Education and PPG Study Program obtained an average of 83.7% of participants strongly agree and 36.3% agree. From the results of this PkM activity, it can improve the competence of educators in implementing Design Thinking as an innovative learning method that is centered on students, so that